Financial participation in Europe: opportunities and risks for employees - Pendleton, Andrew (Brussels, 2019)
"This Policy Brief analyses the main forms by which workers are able to share in the profits and ownership of the companies the work in. It also examines the implications of financial participation for other forms of employee representation, and poses some questions about the practice should be regulated. Its main recommendations are that policies for financial participation should be re-examined in the light of moves to promote it further, and future schemes should be designed to maximise the number of workers who can participate. "